2016
DOI: 10.1016/j.aquatox.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of temperature and metal exposure on the fatty acid composition of cell membranes, antioxidant enzyme activities and lipid peroxidation in yellow perch ( Perca flavescens )

Abstract: The aim of this study was to investigate the combined effects of temperature and metal contamination (cadmium and nickel) on phospholipid fatty acid composition, antioxidant enzyme activities and lipid peroxidation in fish. Yellow perch were acclimated to two different temperatures (9°C and 28°C) and exposed either to Cd or Ni (respectively 4μg/L and 600μg/L) for seven weeks. Superoxide dismutase, catalase, glutathione-S-transferase, glutathione peroxidase activities and glutathione concentration were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 63 publications
5
41
0
Order By: Relevance
“…However, 8 weeks of Cd exposure did not change the mRNA level of scd1 in the brain and muscle of fathead minnow . In addition, Scd1 activity was not affected by 7 weeks of Cd exposure in the muscle of yellow perch . It seems that Cd exposure modified the transcription levels of scd1 in a time‐, tissue‐ and species‐specific manner .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, 8 weeks of Cd exposure did not change the mRNA level of scd1 in the brain and muscle of fathead minnow . In addition, Scd1 activity was not affected by 7 weeks of Cd exposure in the muscle of yellow perch . It seems that Cd exposure modified the transcription levels of scd1 in a time‐, tissue‐ and species‐specific manner .…”
Section: Discussionsupporting
confidence: 90%
“…As an environmental stressor, Cd exposure also induces scd1 expression in common carp . However, recent studies in fathead minnow and yellow perch indicated that Scd1 transcription or activity was not affected by Cd exposure . It seems that upregulation in the activity of Scd1 to recompense the fatty acid profile is species specific during Cd exposure …”
Section: Introductionmentioning
confidence: 97%
“…It was recently reported that membrane disruption by some antimicrobial compounds correlates with lipid peroxidation (Chowhan et al ; Pasquariello et al ). MDA, an important marker of membrane stress, is the main product of membrane lipid peroxidation (Fadhlaoui and Couture ; Zhang et al ). In our study, the extracellular and total MDA contents of GA treatments were significantly higher than those of the control group, which indicated that the membrane permeability had changed, and membrane lipid peroxidation had occurred (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation does exist with the desaturase index and membrane saturation states, as previously established in two fish species, milk fish and the grass carp when subjected to cold acclimation from 25 °C to 15 °C over 21 days (Hsieh & Kuo 2005). Similarly higher desaturase index for SCD was observed in yellow perch (Perca flavescens) acclimated at 9 °C than at 28°C (Fadhlaoui & Couture 2016).…”
Section: Desaturase Index Correlates With Membrane Saturation Statesupporting
confidence: 72%
“…In the present study the desaturase index (DSI) (C16:1c9/C16:0) and (C18:1c9/C18:0) were shown to correlate with the saturation states of the membrane and DSI has been used as a surrogate for the measurement of stearoyl-CoA desaturase (SCD) enzyme activity in membrane remodelling in response to temperature (Fadhlaoui & Couture 2016). The enzyme SCD plays a key role in unsaturation of SFA by catalysing the synthesis of MUFA, primarily by the introduction of the first double bond between the C9 and C10 position of the fatty acid which results in increased membrane disorder and enhanced fluidity (Paton & Ntambi 2009).…”
Section: Desaturase Index Correlates With Membrane Saturation Statementioning
confidence: 78%